PENGARUH KONTROL DIRI TERHADAP KECANDUAN INTERNET PADA MAHASISWA SEMESTER AKHIR PROGRAM PENDIDIKAN DIPLOMA TEKNOLOGI LABORATORIUM MEDIS FAKULTAS PENDIDIKAN VOKASI DAN ILMU KESEHATAN UNIVERSITAS SARI MUTIARA INDONESIA - Sri Ramadhani; Dwi Nursiti; Laksana Tobing; Ainun Mardiayah Larosa (JURNAL PSYCHOMUTIARA, 2021)
The need for the internet makes students use the internet in everyday life. Excessive use of the internet can lead to internet addiction. Self-control is considered to be one of the factors that influence internet addiction. This study aims to determine the effect of self-control on internet addiction in Final Semester Students of the Diploma in Technology Education Program at the Medical Laboratory, Sari Mutiara Indonesia University, Medan. The sampling technique used was purposive sampling technique. The sample in this study were students with male and female categories with a total of 54 students. Data was collected through a measuring instrument in the form of a questionnaire compiled by researchers based on aspects of both self-control variables and internet addiction. The sampling technique in this study is by non-probability sampling. Non-probability sampling is a samplingtechnique that does not provide equal opportunities/opportunities for each element or member of the population to be selected as a sample. In this study, using purposive sampling, which is a technique to determine research samples with certain considerations aimed at making the data obtained later can be more accurate. representative. Based on the problems and theories that have been described above, it can be formulated that there is an influence of self-control on internet addiction in students in the final semester of the Diploma in Technology Education Program, Medical Laboratory, Faculty of Pharmacy and Health Sciences, Sari Mutiara University, Indonesia. Internet addiction behavior. Conversely, the lower the self-control, the higher the internet addiction.